Sediment Grain Size Analysis and Characteristics of Sedimentation Processes in the Bang Berd-Khao Tham Thong Beach, Chumphon Province - Rawadee Meeprasit; Sujaree Bureekul; Suriyan Saramul (Applied Environmental Research)
This study investigated the sedimentological characteristics of the Bang Berd-Khao Tham Thong beach system, which is located along the western shore of the central Gulf of Thailand, an area that is minimally disturbed by human activity and is ideal for studying natural coastal processes. Sediment samples were collected from both coastal and marine environments across four sampling periods (July 2022, September 2022, April 2023, and June 2023). The analysis focused on the grain size distribution, sorting, skewness, kurtosis, and sediment composition, revealing a predominance of medium sand in coastal sediments and increased silt and clay contents in marine sediments. The largest sediment particle size is 466.78 microns. Coastal sediments show a well-sorted size distribution, with a mesokurtic kurtosis. In contrast, sediment samples collected from the marine environment exhibit a poorly sorted size distribution, with leptokurtic kurtosis. Most sediment samples also have symmetrical skewness. Coastal sediments displayed characteristics of tidal influence, with some southern coastal areas exhibiting desert-like conditions due to wind action. The marine sediments were a mixture of shallow marine and fluvial depositional environments. Linear discriminant functions and the CM diagram were used to classify the sediment accumulation environments, identifying four main depositional modes: rolling, rolling and suspension, suspension and rolling and graded suspension. These findings contribute to a deeper understanding of sediment transport and accumulation processes in coastal and marine environments, with implications for coastal management and climate change adaptation strategies.